Increasing the Detection Rate of Congenital Heart Disease During Routine Obstetric Screening Using Cine Loop Sweeps. (1st June 2013) - Scott, Ted E.; Jones, Judy; Rosenberg, Herschel; Thomson, Andrea; Ghandehari, Hournaz; Rosta, Neil; Jozkow, Kim; Stromer, Malka; Swan, Hans
Abstract : Objectives: The purpose of this study was to demonstrate an increase in the detection rate of fetal cardiac defects using 2 cine loop sweeps. Methods: Image reviewers examined a series of 93 cases randomly sorted, including 79 studies with normal findings and 14 studies with abnormal findings. All of the images were assessed by 5 standard criteria. Cases were classified as normal, abnormal, or indeterminate. Reviewers using the conventional approach reviewed 3 still images: the 4‐chamber, left ventricular outflow tract, and right ventricular outflow tract views. Reviewers using the cine loop sweeps viewed 2 grayscale sweeps through the fetal heart in real time. The image sequences were reviewed independently by 2 experts, 3 nonexperts, and 2 sonographers blinded to each others' results. Results: The cine loop sweeps had an increased detection rate of 38% for the nonexperts and 36% for the experts compared with the conventional approach. The cine loop sweeps allowed identification of all cardiac defects by at least 2 of the 7 reviewers; the percentage of cases with false‐positive findings was 3.9%. With the conventional approach, 2 defects went undetected by all reviewers, and 4 defects were found by only 1 reviewer; the percentage of cases with false‐positive findings was 5.4%. Conclusions: The use of cine loop sweeps has the potential to increase the detection of fetal cardiac defects without increasing the rate of false‐positive findings or increasing the interpretation and decision‐making times.